2002
DOI: 10.1046/j.1526-100x.2002.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Restoration in Connecticut: 20 Years of Science and Management

Abstract: In 1980 the State of Connecticut began a tidal marsh restoration program targeting systems degraded by tidal restrictions and impoundments. Such marshes become dominated by common reed grass ( Phragmites australis ) and cattail ( Typha angustifolia and T. latifolia ), with little ecological connection to Long Island Sound. The management and scientific hypothesis was that returning tidal action, reconnecting marshes to Long Island Sound, would set these systems on a recovery trajectory. Specific restoration ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
151
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 42 publications
4
151
0
Order By: Relevance
“…Both of these parameters decrease sharply as salinities exceed 26 ppt (WARREN et al, 2002), and this level was achieved on average in the Upper Impoundment of Potter Pond after tidal restoration. As live P. australis was lost in the Upper Impoundment, it was replaced by an increasing area of open water habitat that was rapidly used by highly mobile nekton such as F. heteroclitus and Palaemonetes spp.…”
Section: Discussionmentioning
confidence: 92%
“…Both of these parameters decrease sharply as salinities exceed 26 ppt (WARREN et al, 2002), and this level was achieved on average in the Upper Impoundment of Potter Pond after tidal restoration. As live P. australis was lost in the Upper Impoundment, it was replaced by an increasing area of open water habitat that was rapidly used by highly mobile nekton such as F. heteroclitus and Palaemonetes spp.…”
Section: Discussionmentioning
confidence: 92%
“…True functional equivalency with a reference system may take decades or longer (Zedler & Callaway 1999). For example, a program begun in 1980 to restore tidal action to marshes off Long Island Sound in Connecticut and evaluated 20 years later by comparing restoration and reference sites found highly variable rates of recovery within and among marshes and that recovery of animal populations took up to two decades or more (Brawley et al 1998, Warren et al 2002. Therefore, to make time-frame criteria more meaningful, performance criteria should be stated in terms of trends as well as target ranges.…”
Section: Approaches To Establishing Performance Criteriamentioning
confidence: 99%
“…Many of these invertebrates are often prey organisms for higher trophic level marsh animals. High tide predators such as fish and crustaceans, and low tide predators like wading and shore birds, depend on the abundance and diversity of invertebrates that occupy the sediments across a range of marsh elevations (MacKenzie et al 2015, Warren et al 2002.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…Support for this has been reported by Fell et al (2000), Burdick et al (1997), andRozsa (1995b) who found that characteristic salt marsh invertebrate communities similar to nearby reference communities established when tidal hydrology was restored. An important qualifier for restored tidal hydrologic connectivity to drive invertebrate community assembly is an adequate supply of propagules, primarily planktonic larvae, and sediment conditions suitable for subsequent survival (Warren et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation